Left atrial reverse remodeling improves sinus restoration following mitral valve replacement: A case report. (September 2021) - Kusumanegara, Jayarasti; Mallapasi, Muhammad Nuralim; Kabo, Peter; Usman, Umar; Syamsuddin, Deni; Faruk, Muhammad
Abstract: Introduction: Mitral stenosis is one of the most common abnormalities in rheumatic heart disease (RHD). These patients often experience atrial fibrillation, due to left atrial dilatation, causing a high risk of thromboembolic events; rhythm or heart rate control are thus important treatment strategies. In patients undergoing surgery, sinus rhythm restoration is not fully understood, and not all surgical patients return to sinus rhythm. We report an adult woman with mitral regurgitation who experienced sinus restoration after mitral valve replacement (MVR) surgery. Case presentation: A 44-year-old woman presented with chief complaints of orthopnea and shortness of breath during activity for 2 months. Electrocardiography (ECG) revealed atrial fibrillation with normal ventricular response, and echocardiography showed severe mitral stenosis with Wilkins score of 10 (3-2-3-2), moderate mitral and aortic regurgitation due to RHD, moderate tricuspid regurgitation with probable pulmonary hypertension, normal left ventricular systolic function, ejection fraction of 60.5% (biplane). MVR surgery was performed using a mechanical mitral valve. Postoperative ECG found sinus rhythm and first-degree AV block. Postoperative echocardiography found a decreased left Atrial volume index of 70.8 mL/m 2, indicating further remodeling of the patient's heart. Conclusion: Sinus restoration sometimes occurs in patients after MVR. The correction procedure causes minimal anatomical changes, particularly the loss of non-conductive and pathological tissue, followed by hemodynamic changes that eventually lead to the left atrial reverse remodeling mechanism. Highlights: Mitral stenosis is one of the most common abnormalities in rheumatic heart disease. Sinus restoration is sometimes found after mitral valve replacement. Non-conductive tissue loss and improved hemodynamics can lead to sinus restoration.